The Impact of Internationalization of Sarbanes-Oxley Act to the U.S. Listed Indonesian Companies - Ahmad Fauzi; Asri Sitompul (RIRAI Publisher, 2020)
In every country the existence of capital markets is fundamental in the development of the economy. Capital market, in addition to its function as a means to gather and allocate the public funds. Numerous companies attempted to fix up in order to get into a stock market and do the Initial Public Offering (IPO). But it is not an easy job, various preparations should be carried out and of course it takes some time and effort and considerable cost. In addition to stock market laws, the market is also governed by various regulations issued by the market authorities and stock exchanges as the SRO. In the U.S., the authority is the SEC and in Indonesia the capital market authority is the OJK. Stock exchanges such as the NYSE in the U.S. and Indonesian Stock Exchange (BEI) in Indonesia also issued various rules regulate all companies listed the shares in the stock exchanges. Internationalization means to bring something local to the international level. The Sarbanes-Oxley Act is supposed to applicable only in the U.S, it is not applicable in Indonesia. But the law is brought from the U.S brought to Indonesia to be applied to Indonesian companies that have the stocks listed with the U.S stock market. The application of the Act brought some problems to Indonesian companies that have to comply with all requirements stipulated in the Act.